Spring-loaded reproduction: effects of body condition and population size on fertility in migratory caribou ( Rangifer tarandus) - Pachkowski, M.; Côté, S.D.; Festa-Bianchet, M. (Canadian Journal of Zoology, 2013)
In many ungulates, female fecundity is affected by body condition and has important effects on population dynamics. In some species, females adopt a conservative strategy, reducing reproductive effort when population density is high. We investigated what factors affect the probability of gestation in adult female caribou (Rangifer tarandus (L., 1758)) from the Rivière-George herd in northern Quebec and Labrador over 5 years that spanned various population sizes and trends. Similar to other populations of migratory caribou, the probability that a female was pregnant in spring increased with body mass and percent body fat. The probability of gestation appeared to be reduced by high infestation of warbles (Hypoderma tarandi (L., 1758)). The proportion of females pregnant varied between years and was lower at high population size. Females of similar mass, however, were pregnant regardless of whether the population was increasing at low density, had reached a peak, or was declining. Compared with other ungulates that reduce maternal expenditure at high density, female caribou of the Rivière-George herd may have a risk-prone reproductive strategy.